Experiences, challenges, and training reflections of nurses in isolation wards during different pandemic prevention policy periods: a qualitative study - Dandan Zhang; Yitong Jia; Yongjun Chen; Qingqing Liao; Meimei Wang; Yin-Ping Zhang (BMC Nursing)
Abstract Background During the pandemic, China’s control policies shifted from nationwide restrictions to precise control and monitoring, which ended with complete relaxation, presenting unique challenges for nurses. Existing qualitative studies mostly focused on the experiences of frontline nurses in the early stages of the pandemic, but they overlooked the dynamic nature of the role changes and adaptation processes as the pandemic evolved. In-depth research into nurses’ experiences across different control phases is crucial for guiding future training to improve preparedness and policy enhancements. Objective To explore the experiences and challenges faced by frontline nurses in China during different phases of pandemic control policies. It also evaluates their training, reflects on the inadequacies of the training, and discusses how these experiences can inform future training programs while offering recommendations to enhance future emergency preparedness. Methods This study employed a qualitative descriptive design to explore the experiences and insights of nurses during the pandemic, as well as their attitudes toward training. Twenty-four frontline nurses from various hospitals in China were recruited using snowball sampling for in-depth interviews, which spanned two months. Data analysis was conducted using Giorgi’s phenomenological approach, involving coding and theme extraction. Results From a content analysis perspective, five main themes were extracted from different stages of control policies during the pandemic: (1) Nurses’ feelings and responses: including early psychological stress and physical discomfort during the pandemic, adaptation and conflicts in isolation management during the rebound period, and later medical resource shortages. (2) Work achievements: covering a sense of mission, personal growth, and recognition. (3) Difficulties and challenges encountered: including initial workflow issues, resource shortages, critical care management gaps, communication barriers during the rebound period, and a decline in staff morale. (4) Training issues: rushed early training, limited content, lack of process and details during the rebound period, inconsistent standards, and lack of enthusiasm for participation. (5) Training improvement recommendations: suggesting an emphasis on training content, reasonable scheduling of training time, various forms of training, multiple assessment methods, and establishment of human resource reserves. Conclusion These findings reveal the challenges faced by frontline nurses during different phases of the pandemic, emphasizing the necessity of comprehensive and systematic nurse training programs. Recommendations include regularly updating training content, enhancing communication and psychological intervention training, diversifying training formats, establishing a mechanism for continuous learning, and exploring personalized training plans to improve nurses’ preparedness in future public health crises.